Effect of charged and ortho substituents on 17O NMR chemical shifts of substituted phenyl tosylates in DMSO. (10th July 2018) - Nummert, Vilve; Piirsalu, Mare; Toom, Lauri; Kesvatera, Tõnu; Leito, Ivo; Koppel, Ilmar A.
Abstract: The 17 O nuclear magnetic resonance chemical shifts for 31 ortho ‐substituted, para ‐substituted, and meta ‐substituted phenyl esters of 4‐methylbenzenesulfonic acid (phenyl tosylates, 4‐CH3 ‐C6 H4 SO2 OC6 H4 ‐X) with the neutral and charged substituents in phenoxy part were measured in DMSO‐ d 6 at 50°C. The chemical shifts, δ ( 17 O), of the sulfonyl (SO2 ) and single‐bonded phenoxy (O─Ph) oxygens for para and meta derivatives in the case of neutral substituents showed a good correlation with the Taft σ I and σ °R substituent constants. The influence of the ortho substituents on the δ ( 17 O) chemical shifts of the sulfonyl oxygens and single‐bonded phenoxy oxygens was found to be described well with the Charton equation: δ ( 17 O)ortho  =  δ ( 17 O)H  +  ρ I σ I  +  ρ R σ °R  +  δE B s when the data treatment was performed separately for electron‐donating + R substituents and electron‐withdrawing − R substituents. The substituent constants, σ °X±, for the charged substituents (4‐N + (CH3 )3 I −, 3‐N + (CH3 )3 I −, 2‐N + (CH3 )3 I −, 4‐COO − N + Bu4, 3‐COO − N + Bu4, 2‐COO − N + Bu4 ) calculated from the δ ( 17 O) chemical shifts for phenyl tosylates in DMSO prove that in DMSO, the compounds involving charged substituents are predominantly in ion pair form and not dissociated into free ions. The same conclusion was drawn recently from the carbonyl IR stretching frequencies, ν CO, and the carbonyl carbon 13 C chemical shifts for substituted phenyl benzoates, C6 H5 CO2 C6 H4 ‐X, in DMSO. It was shown that for ion pairs of the charged substituents in DMSO and concentrated aqueous salt solution, the same substituent constant, σ °X±, could be used. Abstract : Influence of charged and electroneutral ortho, meta, and para substituents on 17 O nuclear magnetic resonance chemical shifts of substituted phenyl tosylates in DMSO was studied.